2013
DOI: 10.1155/2013/764180
|View full text |Cite
|
Sign up to set email alerts
|

Development and Performance Evaluation of Very High Early Strength Geopolymer for Rapid Road Repair

Abstract: High early strength is the most important property of pavement repair materials to allow quick reopening to traffic. With this in mind, we have experimentally investigated geopolymers using low cost raw materials available in Thailand. The geopolymer mortar was metakaolin (MK), mixed with parawood ash (PWA, rubberwood ash) or oil palm ash (OPA) as binder agent. Rubberwood is often used as raw material for biomass power plants in Thailand, especially at latex glove factories and seafood factories, and burning r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…erefore, the AAHFAC could be used as an alternative repair material as reported by several publications [13,14,20,29,[41][42][43]. ere are many reasons such as high compressive strength [44], negligible drying shrinkage [45], low creep [46], good bond with reinforcing steel [47,48], good resistance to acid and sulfate [3,27], fire resistance [49], and excellent bond with old concrete [14,20,28].…”
Section: Resultsmentioning
confidence: 99%
“…erefore, the AAHFAC could be used as an alternative repair material as reported by several publications [13,14,20,29,[41][42][43]. ere are many reasons such as high compressive strength [44], negligible drying shrinkage [45], low creep [46], good bond with reinforcing steel [47,48], good resistance to acid and sulfate [3,27], fire resistance [49], and excellent bond with old concrete [14,20,28].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, ratio of sand to binder is one of the important factor for considering as repair materials which related to a homogeneous matrix of geopolymer binder as reported by Thakur and Ghosh [14]. In order to utilize geopolymer binder as an alternative repair material, many researchers [2,3,[15][16][17][18][19] have studied the setting time, strength development and bonding strength for proving their properties compared with commercial repair materials in the market. As mentioned, the 7-day strength requirement of rapid hardening cementitious materials was 28.0 MPa as per ASTM C928-13 [20], and the initial setting time and minimum strength requirements for repair binder were 30 minutes and 35.0 MPa, respectively, as per ASTM C881/C881M-14 [21].…”
Section: +mentioning
confidence: 99%
“…Moreover, alkali-activated binders have also been used as pavement repair materials (Hawa et al, 2013;Alanazi et al, 2016;Duan et al, 2016a). For the use of alkali-activated binders as repair and reinforcement of damaged notched concrete beam, Phoo-ngernkham et al (2016b) reported that the flexural strength of notched concrete beam filled with the alkali-activated binder made from low calcium fly ash plus granulated blast furnace slag activated with alkali solutions was similar to most commercial repair materials.…”
Section: Introductionmentioning
confidence: 99%